The Relationship Between Soft Skills And Daily Performance Values Of Problem Based Learning Of Students Of The Faculty Of Medicine, Swadaya University Gunung Jati - Cevy Fadhila, Alfiyyah; Setiya Sulistiyana, Catur; Rahadiani Permana, Ouve (Jurnal Health Sains, 2024)
Soft skills are an important attribute in medical practice. PBL is one of the learning methods used by the UGJ Faculty of Medicine, where the assessment process and rubric have adapted soft skills. It is important to know whether there is a relationship between soft skills and the daily PBL performance scores of FK UGJ students. Knowing the relationship between soft skills and the daily PBL performance value of FK UGJ students. This study uses descriptive studies, including analytical observational research, primary data in the form of questionnaires, and secondary data in the form of an archive of PBL performance values. 95.4% (228) of the 239 respondents had sufficient problem-solving soft skills, 97.9% (234) of the 239 respondents had sufficient initiative soft skills, 94.6% (226) of the 239 respondents had sufficient soft skills of integrity, 92.1% (220) of the 239 respondents had sufficient communication soft skills, 88.3% (211) of the 239 respondents had sufficient teamwork soft skills. PBL performance values show quite wide variations. Most students score between 35.0 - 40.0. The results of the research show that there is a significant relationship between the five aspects of soft skills and the daily PBL performance scores of FK UGJ students. There is a significant relationship between the five aspects of soft skills and the daily PBL performance scores of FK UGJ students